THE ROLE OF PERSONAL ABILITIES AND FAMILY SUPPORT IN INCREASING ENTREPRENEURIAL INTEREST: E-COMMERCE MODERATION - Anis, Nusron; Windi , Eka Prasasti (STIE PGRI Dewantara Jombang, 2025)
The imbalance between the number of job seekers and available employment opportunities is a major cause of unemployment in Indonesia. Many university graduates aim to work in companies, yet the misalignment between higher education and labor market demands hinders graduate absorption into the industry. To address this, universities have introduced initiatives to enhance entrepreneurial knowledge and skills, aiming to foster students' interest in entrepreneurship. This study investigates the influence of personal abilities and family support on entrepreneurial interest, and examines the moderating role of e-commerce. The study involved 94 respondents, selected using the Slovin formula, from a population of students who had completed entrepreneurship and creative economy courses. The results indicate that personal abilities, family support, and e-commerce significantly affect entrepreneurial interest. Furthermore, e-commerce does not moderate the effect of personal abilities on entrepreneurial interest but does strengthen the influence of family support. These findings highlight the importance of both individual and contextual factors in shaping students' entrepreneurial intentions.